Historyczny krajobraz i struktury. Refleksje nn temat rzymskiej Galicji - Pereira Menaut, Gerardo (Acta Universitatis Lodziensis. Folia Archaeologica, 1990)
The author states that the particular character of roman Galicia, in concern to public works, is nothing but a practically total absence of any public works. Further, he adds that the country of roman Galicia is not structured by cities. The comnunities of roman Galicia had a particular form of organization. They were constituted by a number of semi-autonomous castrocommunities, but no urban centre. The need for public works such as circuses, theatres, curiae etc. was not generated in roman Galicia. There must have been some public works as water-conductions and other essential implements for the life of even a little community. But these were not what we here call public works. They have, in fact, most frequently left no rests.